Spatial delineation on marine environmental characteristics using fuzzy c-means clustering method - E.D. Lusiana; S. Astutik; N. Nurjannah; A.B. Sambah (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Conservation efforts are often prioritized on a large spatial scale because information about local ecosystems is frequently lacking. Therefore, comprehensive spatial classification of a region’s environmental characteristics is essential for effective marine conservation. This study aimed to construct geophysical and chemical environmental delineation of the Lesser Sunda Islands which are located in Indonesia. This area is an ecoregion in the coral triangle that has been a primary concern of global biodiversity conservation strategies.METHODS: This study utilized eleven global environmental variables that were accessed from global marine databases. After performing a principal component analysis, a fuzzy C-means clustering technique was used to classify the region into groups based on environmental characteristics in term of seasonal variability. It was expected that the areas within each group would have identical attributes and ecological processes.FINDINGS: The results suggested that the marine environmental factors in Lesser Sunda can be simplified using a principal component analysis technique: 6 principal component factors explained 81.06 percent of the overall raw data variability for the wet season, and 7 principal component variables explained 84.51 percent of the overall raw data variability for the dry season. Then, the area can be delineated into 5 groups (wet season) and 10 groups (dry season) with different environmental characteristics. This method's classified groups principally inferred the Indian Ocean and Bali Sea, Savu Sea and Flores Sea, and Banda Sea as distinct clusters. In particular, the group that included the Indian Ocean had characteristics including lower nitrate and sea surface temperature concentrations, as well as higher potential hydrogen salinity and distance from the shore.CONCLUSION: The findings of this study showed that the single marine conservation area in Lesser Sunda is not sufficient to adequately represent the physicochemical dynamics in the area. The proposed delineation result will supplement the existing bioregion classification of marine areas, such as the Marine Ecoregions of the World. Moreover, it is also consistent with existing conservation programs, including the notable national marine protected areas of the Savu Sea. Nevertheless, the acknowledged biogeographic group of the Indian Ocean indicates that countries must work together to successfully manage marine protected areas and achieve their conservation objectives. This work serves as a baseline for both academic research and ecological assessment, and it will contribute to marine protected areas strategies and conservation efforts in the Lesser Sunda Islands.